Laboratory and field evaluation of polymerase chain reaction assays for diagnosis of zoonotic tuberculosis in bovine post mortem samples - PRASAD, CHENDU BHARAT; VISE, ESTHER; DANDAPAT, PREMANSHU; BANIK, AMIT; KADER, NUR ABDUL; MILTON, A A P; WAHLANG, LAVINIA; GHATAK, SANDEEP; SEN, ARNAB; DAS, SAMIR (The Indian Journal of Animal Sciences, 2022)
The diagnosis of zoonotic tuberculosis revolves around detection of pathogen by gold standard culture method. In the live animals, tuberculin testing and interferon gamma assays are the options with their own limitation of specificity and cost effectiveness respectively. Clinical examination along with the affordable methods can lead to a definitive diagnosis which could help in decision making for not only the individual animal but also for the whole farm. During post-mortem examination, the post-mortem lesions with visible tubercle and acid fast staining give a fair idea of tuberculosis infected carcass for tuberculosis. The molecular testing of tissue samples with proven mycobacterial genus, Mycobacterium tuberculosis complex (which includes M. bovis also) and M. bovis species-specific primers can add to the diagnostic strength for bovine tuberculosis. In this regard, we evaluated sequential PCRs for mycobacterial genus specific primer (hsp65), M. tuberculosis complex specific primer (IS6110 & IS1081) and M. bovis specific primer (RD4 and 500 bp) in spiked and field tissue samples of cattle. The research was carried out in 2019-20 in Division of Animal Health for framing out a diagnostic confirmation protocol for TB infected cattle on tissue samples. All the PCR assays were almost equally efficient in detection of M. bovis in spiked samples, if supported by an efficient DNA extraction method which is the foremost limiting factor. It was concluded that a combination of minimum of two assays can give a definitive result along with the support of the clinical history or post mortem outcome of the animals.